Remyelination in humans due to a retinoid‐X receptor agonist is age‐dependent. Issue 7 (19th May 2022) - McMurran, Christopher E.; Mukherjee, Trisha; Brown, J William L.; Michell, Andrew W.; Chard, Declan T.; Franklin, Robin J. M.; Coles, Alasdair J.; Cunniffe, Nick G.
Abstract: Remyelination efficiency declines with advancing age in animal models, but this has been harder to demonstrate in people with multiple sclerosis. We show that bexarotene, a putatively remyelinating retinoid‐X receptor agonist, shortened the visual evoked potential latency in patients with chronic optic neuropathy aged under 42 years only (with the effect diminishing by 0.45 ms per year of age); and increased the magnetization transfer ratio of deep gray matter lesions in those under 43 years only. Addressing this age‐related decline in human remyelination capacity will be an important step in the development of remyelinating therapies that work across the lifespan.